2016
DOI: 10.1007/s10895-015-1747-2
|View full text |Cite
|
Sign up to set email alerts
|

Colorful Polyelectrolytes: An Atom Transfer Radical Polymerization Route to Fluorescent Polystyrene Sulfonate

Abstract: A labeled green fluorescent polystyrene sulfonate (LNaPSS) has been synthesized using atom transfer radical polymerization of a styrene sulfonate monomer with a fluorescent co-monomer, fluorescein thiocyanate-vinyl aniline. As a result this 100 % sulfonated polymer contains no hydrophobic patches along the chain backbone besides the fluorescent marker itself. The concentration of the fluorescent monomer was kept low to maintain the characteristic properties of the anionic polyelectrolyte, LNaPSS. ATRP conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It forms an active complex for ATRP yet remains stable toward disproportionation . The Cu/Bpy system has been previously reported for the synthesis of NaPSS, and has recently been shown to be a relatively stable active catalyst system in an aqueous environment . A higher deactivation rate constant than expected results in narrow molecular weight distributions .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It forms an active complex for ATRP yet remains stable toward disproportionation . The Cu/Bpy system has been previously reported for the synthesis of NaPSS, and has recently been shown to be a relatively stable active catalyst system in an aqueous environment . A higher deactivation rate constant than expected results in narrow molecular weight distributions .…”
Section: Resultsmentioning
confidence: 99%
“…Iddon et al demonstrated room temperature syntheses of NaPSS in a mixed H 2 O/MeOH solvent, but the molecular weights did not exceed 25,000 g mol −1 and Ð values were high (1.26–2.03) . Huberty et al produced NaPSS via an aqueous ATRP with molecular weights of 30,000–2 × 10 5 g mol −1 and Ð values in the range of 1.01–1.24 but the reaction was reported to lack reproducibility …”
Section: Introductionmentioning
confidence: 99%